1994
DOI: 10.3109/02770909409044826
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Conventional Press-and-Breathe Metered-Dose Inhaler Technique in 501 Patients

Abstract: Conventional press-and-breathe metered dose inhalers (MDIs) are widely prescribed but are often difficult for many patients to properly use. A total of 501 patients from different medical specialties were enrolled in this study, which evaluated how the patients used their MDIs. Using a conservative method (minimum number of errors) of determining errors, we found that 388 (77.5%) of the patients made at least one error when demonstrating how they use their MDI for two observers. Using a liberal (maximum number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 2 publications
6
51
1
4
Order By: Relevance
“…Other studies found a high prevalence of noncompliance with MDI in COPD [31] or asthmatic [32] patients, and even in medical personnel [33]. This, together with the fact that a high proportion of the patients in the present study reported having been taught the inhaler manoeuvre (and rechecked), and that there are less mistakes made with dry powder devices than with MDI, could suggest that the problem is inherent to the MDI, rather than related to the patients or physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found a high prevalence of noncompliance with MDI in COPD [31] or asthmatic [32] patients, and even in medical personnel [33]. This, together with the fact that a high proportion of the patients in the present study reported having been taught the inhaler manoeuvre (and rechecked), and that there are less mistakes made with dry powder devices than with MDI, could suggest that the problem is inherent to the MDI, rather than related to the patients or physicians.…”
Section: Discussionmentioning
confidence: 99%
“…One of the biggest challenges associated with effective lung delivery using MDIs is the difficulty some patients have actuating the device at the appropriate point in the inspiratory cycle (68,69). Lung deposition is reduced (sometimes, greatly) when the patient actuates the device before or after inhaling (70).…”
Section: Breath Actuationmentioning
confidence: 99%
“…Therefore, they are not appropriate for young children, people with arthritis and many elderly patients. Studies have shown that 50% to 80% of adults have diffi culty using a pMDI [4][5][6]. The breath-actuated pMDIs (e.g.…”
Section: Evidence To Datementioning
confidence: 99%